Optimized laboratory techniques for assessing the quality of pre-stripped DMEK grafts - Tomy Sagnial; Sandrine Ninotta; Paul Goin; Inès Aouimeur; Louise Parveau; Sylvain Poinard; Oliver Dorado Cortez; Olfa Ben Moussa; Hanielle Vaitinadapoule; Anne-Sophie Gauthier; Philippe Gain; Gilles Thuret; et al. (Scientific Reports)
Abstract This study addressed limitations in calcein-AM-based endothelial viability assays, specifically focusing on pre-stripped DMEK grafts. Key challenges included the suboptimal calcein staining and the incompatibility of the viability assay with subsequent immunofluorescence (IF). Using human corneal grafts, we employed two strategies to optimize calcein staining. Firstly, we improved calcein staining in corneal endothelium by adjusting calcein-AM concentration and diluent, resulting in a threefold increase in fluorescence intensity with 4 µM calcein in Opti-MEM compared to the conventional 2 µM calcein in PBS. Secondly, introducing the trypan blue (TB) post-viability assay greatly reduced non-specific fluorescence, enhancing the contrast of calcein staining. This improvement significantly and importantly decreased both inter-operator’s variability and the time required for viability counting. For the subsequent double IF, an extensive wash is recommended on the fixed and permeabilized graft after the viability assay, which was carried out using Hoechst-Calcein (HC) labeling. The simple technical tips outlined in this study are not only effective for pre-stripped DMEK grafts but may also prove beneficial for other types of corneal grafts, such as PK and DSAEK.